Qualitative Analysis of The Millennial Generation's Perspective On Social Welfare Through Sharia-Based Economic Development - Hariyono, Hariyono; Ferdiansyah, Dimas (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
This research aims to analyze the millennial generation's perspective on social welfare through sharia-based economic development. Using a qualitative approach, data was collected through in-depth interviews with a number of millennials who have an understanding of sharia economics. The research results show that the millennial generation has a positive view of the concept of social welfare resulting from sharia-based economic development. They assess that sharia economic principles, such as justice, transparency and social responsibility, can contribute significantly to improving social welfare. Apart from that, the millennial generation also sees that the implementation of sharia economics can be a solution to reduce economic and social inequality in society. This research concludes that wider understanding and acceptance of sharia economics among the millennial generation can support sustainable social and economic development.